Nursing Care of Head Injury Patient with Epidural Hematoma - มะลิวัลย์, อำพร (Journal of Preventive Medicine Association of Thailand, 2018)
Traumatic brain injury and epidural hematoma could cause crippling and lifelong physical, emotional, cognitive, and social disabilities that leave patients totally dependent and needing placement in long-term care facilities, and death, the worst case. Emergency care is vital for traumatic brain patient especially the patient who has subdural hemorrhage. As a result, emergency nursing is essential in order to assess symptoms and sign, physically and mentally, and implement the treatment plans for the best possible recovery. Nursing care plan and nursing intervention that aim to recover vitals organ and protect IICP, the most important complication which needs principle of pathology and can result in brain trauma. Traumatic brain injury case study paves the way of nursing implementation which is responsive to fulfill basic human needs in the most threatening situation and respective to human dignity.